2017
DOI: 10.18632/oncotarget.19176
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase JMJD2C: epigenetic regulators in tumors

Abstract: Histone methylation is one of the major epigenetic modifications, and various histone methylases and demethylases participate in the epigenetic regulating. JMJD2C has been recently identified as one of the histone lysine demethylases. As one member of the Jumonji-C histone demethylase family, JMJD2C has the ability to demethylate tri- or di-methylated histone 3 and 2 in either K9 (lysine residue 9) or K36 (lysine residue 36) sites by an oxidative reaction, thereby affecting heterochromatin formation, genomic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Antimycin, a mitochondrial electron transport chain inhibitor, has been shown to prevent the growth of lung cancer cells [ 33 ]. GSK-J4 is an inhibitor of several histone demethylases and has been proposed as a potential cancer therapeutic agent [ 34 ]. We found that all AR-positive cell lines tested were more sensitive to inhibition of mTOR (EC 50 < 100 nM) relative to the NCI-H660 cell line (EC 50 > 100 µM) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antimycin, a mitochondrial electron transport chain inhibitor, has been shown to prevent the growth of lung cancer cells [ 33 ]. GSK-J4 is an inhibitor of several histone demethylases and has been proposed as a potential cancer therapeutic agent [ 34 ]. We found that all AR-positive cell lines tested were more sensitive to inhibition of mTOR (EC 50 < 100 nM) relative to the NCI-H660 cell line (EC 50 > 100 µM) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…CFH was also found to have a novel connection with the JMJD2C gene, a histone lysine demethylase. JMJD2C has been reported to play a crucial role in the progression of breast cancer, prostate carcinomas, osteosarcoma, and blood neoplasms, thus indicating that JMJD2C represents a promising anti-cancer target [ 39 , 40 , 41 ]. These findings also suggest that JMJD2C may have an important role in AMD.…”
Section: Resultsmentioning
confidence: 99%
“…At first, we detected the expression of histone-modifying enzymes in E-piPSCs and found that KDM4C could be a candidate. Unlike many other histone-modifying enzymes, KDM4C demethylates H3K36me3/2 and H3K9me3 at the same time [ 22 ]. However, the function of KDM4C is always hard to determine.…”
Section: Discussionmentioning
confidence: 99%